Hubungan Self-Care Management Dengan Kualitas Hidup Pasien Hemodialisis - Aditiya, Dentha; Widiastuti, Agung; Musta’in (Borneo Nursing Journal (BNJ), 2026)
Background: A patient’s quality of life remains significantly influenced by their ability to perform self-care management, although hemodialysis therapy can help maintain their function. This self-care management includes adherence to fluid restrictions, dietary adjustments, taking medications as prescribed, and undergoing regular hemodialysis.Objective: This study aimed to determine the relationship between self-care management ability and the quality of life of patients undergoing hemodialysis. Methods: This quantitative study employed a descriptive correlational design with a cross-sectional approach. A total sampling technique was used to recruit 60 respondents. Data were analyzed using the Spearman Rank correlation test. Results: The univariate analysis showed that most respondents had good self-care management ability (27 respondents; 45.0%), while the majority had a good quality of life (28 respondents; 56.7%). The results of the Spearman Rank test revealed a p-value of 0.000 and a correlation coefficient (r) of 0.603, indicating a statistically significant positive relationship between self-care management and the quality of life of patients undergoing hemodialysis. Conclusion: The better the self-care management ability of patients undergoing hemodialysis, the better their quality of